Evolution of salary differences between men and women in six Latin American countries (2004)
This study investigates the evolution of salary differences and other aspects related to the labor activities of men and women in Latin America. The analysis compares six countries—Argentina, Brazil, Colombia, Costa Rica, Honduras, and Uruguay—which were selected based on the information available during the study period. Each country, with the exception of Honduras, was observed three times: 1) the early 1980s, 2) the late 1980s, and 3) the late 1990s.1 The data used were derived from household surveys, which offer ample opportunities for analyzing important aspects of how labor markets function in these countries; at the same time, they restricted the possibility of comparing countries because of differences in methodologies and coverage.